Current Patterns of Care for Patients with Extensive‐Stage SCLC: Survey of U.S. Radiation Oncologists on Their Recommendations Regarding Prophylactic Cranial Irradiation. Issue 8 (August 2016) - Jain, Aditya; Luo, Jia; Chen, Yiyi; Henderson, Mark A.; Thomas, Charles R.; Mitin, Timur
ABSTRACT : Introduction: : Conflicting data from randomized clinical trials incite the debate over the appropriate use of prophylactic cranial irradiation (PCI) for patients with extensive‐stage SCLC (ES‐SCLC) who achieve clinical response to systemic chemotherapy. The current pattern of practice among U.S. radiation oncologists is unknown. Methods: : We surveyed practicing U.S. radiation oncologists through a short online questionnaire. Respondents' characteristics and their self‐rated knowledge base were analyzed for association with their treatment recommendations. Results: : We received 473 responses from practicing U.S. radiation oncologists. More than half of the respondents had been practicing for more than 10 years after completing residency training, and 70% had treated more than 10 patients with lung cancer per year. Of the respondents, 90% recommended brain magnetic resonance imaging (MRI) before initiation of PCI and 98% recommended PCI for patients with ES‐SCLC after systemic chemotherapy. Half of the respondents followed their patients with brain MRI after completion of PCI. One‐third of the respondents prescribed memantine to patients undergoing PCI. Among the respondents, recent graduates ( p = 0.004) and physicians practicing in academic centers ( p = 0.005) were more likely to prescribe memantine. Self‐rated knowledge base was not associated with any treatment recommendations. Conclusions: : Our analysis revealed that among the respondents, there was a very high adherence to current National Comprehensive Cancer Network guidelines, which recommend providing universal PCI and obtaining brain MRI before initiation of PCI for patients with ES‐SCLC with clinical response to systemic chemotherapy. These guidelines and practice patterns are not supported by clinical evidence because patients in the European Organization for Research and Treatment of Cancer trial did not undergo brain MRI before PCI and the Japanese randomized trial has shown a possible detrimental effect of PCI on overall survival when brain MRI was incorporated. A critical reevaluation of current guidelines is essential to determine the appropriate management of these patients.